WIJI THUKUL'S TEXTUAL STRATEGY IN ITS SYMBOLIC CONTESTATION IN INDONESIAN LITERATURE ARENA: PIERRE BOURDIEU'S CULTURAL PRODUCTION ARENA STUDY (STRATEGI TEKSTUAL WIJI THUKUL DALAM KONTESTASI SIMBOLIKNYA DI ARENA SASTRA INDONESIA: STUDI ARENA PRODUKSI KULTURAL PIERRE BOURDIEU) - Bambang Eko Hari Cahyono; Indrya Mulyaningsih; Panji Kuncoro Hadi (Universitas PGRI Sumatera Barat, 2021)
Poetry is a means of conveying ideas. Wiji Thukul is a poet who was allegedly lost because of his poetry. This study describes the textual strategy or strategy of writing poetry that Wiji Thukul took in his symbolic contestation in the Indonesian literary arena during the New Order era. This research uses Pierre Bourdieu's cultural production theory to describe and explain Wiji Thukul's literary problems, both intrinsic and extrinsic, simultaneously. The data source of this research is the poetry anthology written by Wiji Thukul. The research data is in texts related to the textual strategy of writing Wiji Thukul's poetry on his symbolic contestation during the New Order era. Data were collected through document study and interviews. Data were analyzed with content analysis based on the mechanism of Krippendrof, including a) identifying Wiji Thukul's textual strategy in his symbolic contestation, which was used as material for analysis, b) classifying analysis units according to the problem in the study, c) conducting unit analysis to explore the findings that have identified, and d) determine aspects of the findings to make inferences and draw conclusions. The results of this study: 1) Wiji Thukul used a textual strategy by writing romantic-religious poetry from 1980-1985, 2) Wiji Thukul used a textual strategy by writing critical social poetry from 1985-1990, and 3) Wiji Thukul used a strategy textual by writing party poetry in the period 1990-1998.